2014
DOI: 10.1103/physrevlett.112.116802
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Quantum Jumps of a Single Quantum Dot Spin Using Submicrosecond Single-Shot Optical Readout

Abstract: Single-shot read-out of individual qubits is typically the slowest process among the elementary single-and two-qubit operations required for quantum information processing. Here, we use resonance fluorescence from a single-electron charged quantum dot to read-out the spin-qubit state in 800 nanoseconds with a fidelity exceeding 80%. Observation of the spin evolution on longer timescales reveals quantum jumps of the spin state: we use the experimentally determined waitingtime distribution to characterize the qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 16 publications
1
76
2
Order By: Relevance
“…Both multi-shot [71,72] and single-shot [73] spin readout has been demonstrated using this technique in the Faraday configuration. But the reported single-shot readout fidelity is only ∼ 82% [73], limited by the collection efficiency of the emitted photons and the imperfect cycling transitions.…”
Section: Spin Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Both multi-shot [71,72] and single-shot [73] spin readout has been demonstrated using this technique in the Faraday configuration. But the reported single-shot readout fidelity is only ∼ 82% [73], limited by the collection efficiency of the emitted photons and the imperfect cycling transitions.…”
Section: Spin Measurementmentioning
confidence: 99%
“…Both multi-shot [71,72] and single-shot [73] spin readout has been demonstrated using this technique in the Faraday configuration. But the reported single-shot readout fidelity is only ∼ 82% [73], limited by the collection efficiency of the emitted photons and the imperfect cycling transitions. In the Faraday geometry, one can also optically measure the spin via the spin-dependent Kerr or Faraday rotation of a detuned laser [74][75][76].…”
Section: Spin Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Both time-averaged 35,36 and single-shot 19 spin readout has been experimentally realized for a charged quantum dot with a magnetic field applied in the Faraday configuration. However realizing single-shot readout operation in Voigt configuration is more desired because this geometry is the prerequisite for all-optical coherent spin manipulation 37,38 .…”
Section: Analysis Of Success Probabilitymentioning
confidence: 99%
“…Previous studies have demonstrated single-shot readout with resonance fluorescence in a number of qubit systems, including cold Rubidium atoms [11][12][13] , trapped Calcium 14 and Ytterbium 15 ions, nitrogen vacancy centers 16,17 , quantum dot molecules 18 , and singly charged quantum dot spins with a magnetic field applied parallel to their growth direction (Faraday configuration) 19 .…”
Section: Introductionmentioning
confidence: 99%